LINGUISTIC ANALYSIS OF EUPHEMISM RELATE TO FRIENDSHIP IN ENGLISH AND UZBEK LANGUAGE. (Journal of Universal Science Research, 2023)
The purpose of this article is to cover linguistic issues of translation of social euphemisms in the Uzbek language, the theoretical and practical significance of the work is that it is possible to apply the main point of view and conclusions later on the study of this topic.